1998
DOI: 10.1108/07363769810240545
|View full text |Cite
|
Sign up to set email alerts
|

Consumer equity in relationship marketing

Abstract: The paper examines the current state of relationship marketing in the consumer services market. It questions whether relationships are mutually beneficial to suppliers and customers and argues that the relationship is managed by the retailer primarily for their gain whereas the customer might benefit more from alternative, immediate rewards. This leads to a consideration of how value and equity within relationship marketing might be viewed using social psychology as a basis for re‐examining the nature of suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 27 publications
(21 reference statements)
0
37
0
Order By: Relevance
“…The usefulness of the concept is limited by the characteristics of the product or service. 11 In one of the few empirical investigations of this question, Pressey and Mathews found that relationship The first research question examines the claim that: 'Relationship marketing is conceptually distinct from transaction marketing, direct marketing, database marketing, loyalty marketing and retention marketing on the basis that these are tactical, while relationship marketing focuses on long-term interaction leading to social bonds.' The first research question is:…”
Section: Relationship Marketing In B2c Exchangesmentioning
confidence: 99%
“…The usefulness of the concept is limited by the characteristics of the product or service. 11 In one of the few empirical investigations of this question, Pressey and Mathews found that relationship The first research question examines the claim that: 'Relationship marketing is conceptually distinct from transaction marketing, direct marketing, database marketing, loyalty marketing and retention marketing on the basis that these are tactical, while relationship marketing focuses on long-term interaction leading to social bonds.' The first research question is:…”
Section: Relationship Marketing In B2c Exchangesmentioning
confidence: 99%
“…Research has also shown that customers are aware that mutual gain is not present in all relationships and, therefore, are not willing to build relationships and share personal information with unknown organizations (Phelps, Nowak, and Ferrell 2000;Szmigin and Bourne 1998). For example, according to Sheenan and Hoy (2000), consumers' willingness to provide personal information largely depends on the strength of the their relationship with the requesting company.…”
Section: The Impact Of Willingness To Share Information On Customer Lmentioning
confidence: 99%
“…However, an approach which relies heavily upon direct mail and database marketing, as a "blunt" instrument to reach large numbers of customers will detract from a relationship approach (Dibb and Meadows 2001). The kind of relationship desired, which refers to anything from a full-blooded long-term relationship to a one-off transaction, has to be dependent, on the one hand, on what the customer wants, and on the other, on how well the supplier can match that (Szmigin and Bourne 1998). Since companies and individual consumers act out of self-interest, it cannot make sense to have an approach that rewards the supplier but not the customer.…”
Section: Relationships In Consumer Markets?mentioning
confidence: 99%